2015
DOI: 10.1124/mol.115.101394
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mode Selection Determines the Action of Ecstasy Homologs at Monoamine Transporters

Abstract: Determining the structural elements that define substrates and inhibitors at the monoamine transporters is critical to elucidating the mechanisms underlying these disparate functions. In this study, we addressed this question directly by generating a series of N-substituted 3,4-methylenedioxyamphetamine analogs that differ only in the number of methyl substituents on the terminal amine group. Starting with 3,4-methylenedioxy-N-methylamphetamine, 3,4-methylenedioxy-N,N-dimethylamphetamine (MDDMA) and 3,4-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 53 publications
6
52
0
Order By: Relevance
“…The data reported here for MDC differ somewhat from findings with 3,4-methylenedioxyamphetamine (MDA), the analogous N-demethylated metabolite of MDMA. We and others have shown that MDA and MDMA display nearly identical potency and selectivity as substrate-type releasers at monoamine transporters in vitro (McKenna et al, 1991;Sandtner et al, 2016;Wichems et al, 1995). Interestingly, HHMC was found to be a potent and selective substrate for DAT and NET, with a DAT/SERT ratio of 155 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here for MDC differ somewhat from findings with 3,4-methylenedioxyamphetamine (MDA), the analogous N-demethylated metabolite of MDMA. We and others have shown that MDA and MDMA display nearly identical potency and selectivity as substrate-type releasers at monoamine transporters in vitro (McKenna et al, 1991;Sandtner et al, 2016;Wichems et al, 1995). Interestingly, HHMC was found to be a potent and selective substrate for DAT and NET, with a DAT/SERT ratio of 155 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may not apply to all model systems. Sandtner et al (2016) reported higher potencies for release than for uptake for MDMA at the three transporters using rat brain synaptosomes, whereas MDMA was 3-, 3-, and 18-fold less potent for release compared with uptake at hNET, hSERT, and hDAT, respectively (Tables 2 and 3). The release models are quite different, with HEK cells expressing a single transporter with no blocking agents required, and the superfusion assay involved continuous removal of released substrate from the reaction, compared with rat brain synaptosomes that require blockade of VMAT2 as well as blockade of other transporters, and the "static" release assay does not remove released neurotransmitter from the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The n-pyrrolidino substituent on 4-MePPP is sterically repulsed by bulky side chains in SERT that are found in the orthosteric binding pocket as delineated by the Leu-T structural model, which may account for the low affinity of this entire series for SERT (Saha et al, 2015). The pure transporter inhibitor activity of this group may be due to the n-pyrrolidino substituent, as Sandtner et al (2016) observed that interactions with critical aspartate residues of DAT and SERT are necessary for substrate activity, and secondary or tertiary substitution on nitrogen inhibits interaction with these residues. The high selectivity for hDAT over hSERT suggests that these compounds may have high abuse liability, consistent with the ability of a-PBP and a-PVP to fully substitute for discriminative stimulus effects of both cocaine and METH and to produce conditioned place preference (Gatch et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Structure–activity relationship (SAR) studies as well as docking of selected cathinones into protein homology models of hDAT and hSERT revealed the first insights into the molecular basis of transporter selectivity. 15,17,18 …”
Section: Introductionmentioning
confidence: 99%